Adjustment in the takeoff phase of 1-m springboard forward dives - Sayyah, M.; King, M. A.; Hiley, M. J.; Yeadon, M. R. (ISBS Proceedings Archive (Michigan), 2018)
The aim of this study was to investigate whether any adjustment is made during the board contact phase of 1-m springboard forward dives. Variability of body orientation angle at landing from hurdle (touchdown) and at takeoff together with joint angle time histories of 15 forward pike dive takeoffs, performed by an international diver, were determined using video analysis. A computer simulation model of a diver and springboard was used to determine the effects of perturbations of initial conditions on takeoff variability. The variation at takeoff obtained in the simulation outcome was much greater than in the actual performance, indicating that the diver made adjustments during the board contact phase. The diver varied his body configuration during the board recoil phase to adjust his body orientation, leading to low variability at takeoff.